2022
DOI: 10.1186/s12877-022-03072-w
|View full text |Cite
|
Sign up to set email alerts
|

Correlates to psychological distress in frail older community-dwellers undergoing lockdown during the COVID-19 pandemic

Abstract: Background This study identifies correlates of the lockdown’s psychological distress in frail older community-dwellers (Catalonia, Spain). Methods Participants from a community frailty intervention program, with a comprehensive geriatric assessment within the 12-months pre-lockdown and COVID-19 free during the first pandemic wave (March–May 2020), underwent a phone assessment past the lockdown to assess COVID-19-related emotional distress (DME) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Older adults frailty reported more psychological distress during the COVID-19 pandemic [39]. High prevalence (84.9%) risk of experiencing moderate-to-high psychological distress [67].…”
Section: Mental Healthmentioning
confidence: 97%
See 1 more Smart Citation
“…Older adults frailty reported more psychological distress during the COVID-19 pandemic [39]. High prevalence (84.9%) risk of experiencing moderate-to-high psychological distress [67].…”
Section: Mental Healthmentioning
confidence: 97%
“…The analysis of the extracted papers indicated that the general mental health of frail older adults deteriorated during the COVID-19 pandemic [39,46,48,49,67]. Depressive mode and anxiety are two major psychological effects of the pandemic on frail seniors [33,48,54,55,62,63].…”
Section: Psychological Impactsmentioning
confidence: 99%